(untitled) (European Journal of Pure and Applied Mathematics, 2010)
In this paper, we introduce a new subclass of meromorphic multivalent functions associated with Wright generalized hypergeometric function and obtain new results for this class by the application of Briot-Bouquet differential subordination. Â